Efficacy of whitening oral rinses and dentifrices on color stability of bleached teeth - Muhammet Karadas (Acta Biomaterialia Odontologica Scandinavica)
Objective: This study aimed to evaluate the effect of whitening toothpastes and mouthrinses on the color stability of teeth bleached with 16% carbamide peroxide (CP) after immersion in coffee solution. Materials and methods: Specimens obtained from bovine incisors were bleached with 16% CP for 14 days. After bleaching, the specimens were stained in coffee solution for 24 h and randomly divided into eight groups according to the following products (n = 10): distilled water (control group, DW), Scope White mouthrinse (SW), Crest 3D White mouthrinse (CWR), Crest 3D White toothpaste (CWT), Crest 3D White toothpaste and Crest 3D White mouthrinse (CWT + CWR), Listerine Whitening toothpaste (LWT), Listerine Whitening mouthrinse (LWR), and Listerine Whitening mouthrinse and Listerine Whitening toothpaste (LWR + LWT). Color measurements were conducted using a spectrophotometer. The data were assessed by analysis of variance for repeated measures and Tukey’s multiple comparison test (p < 0.05). Results: Immersion in coffee solution after bleaching caused perceptible staining on tooth specimens (ΔE > 3.46). The whitening effect of CWR on teeth stained after bleaching was significantly greater than that in the other groups (p < 0.001). Tooth whitening (ΔE) in each group showed no significant difference from 6 to 12 weeks (p > 0.05). The combination of mouthrinse and toothpaste did not increase the degree of tooth whitening. Conclusion: Whitening mouthrinse and toothpaste had similar effects on the control group in terms of whitening of teeth stained after bleaching. Nevertheless, Crest 3D White mouthrinse produced the greatest recovery whitening effect among all the products tested.